2008
DOI: 10.1007/s12149-007-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic abilities of Ga-SPECT for head and neck lesions

Abstract: This study revealed the marked superiority of SPECT images over planar images in terms of the ability to detect primary tumors and tumor metastasis to cervical lymph nodes. Furthermore, the primary T1 tumor detection rate of SPECT images was higher than that of CT images. On the basis of these results, the concomitant use of SPECT is highly recommended when Ga scintigraphy is performed to check for malignant head/neck tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…While several of the radiometals such as 67 Cu and 90 Y are used in oncology as radiotherapeutics, the remainder of this discussion will focus on the incorporation of In, Cu, Ga, Y, and Zr radiometals into radiopharmaceuticals for the diagnostic imaging of cancer. Moreover, while numerous radiopharmaceuticals have been prepared to detect biomarkers such as the folate receptor, ,, the neurotensin receptor, , oxytocin receptor expressing tumors, apoptosis using annexin-5, urokinase-type plasminogen activator receptor (uPAR), matrix metalloproteinases (MMPs), , Met-expression, antigens in head-and-neck cancer, , lymphoma, non-Hodgkin’s lymphoma, and esophageal and pancreatic cancer, , the remainder of this discussion will be further confined to several biomarkers that have received the most attention and include the integrin α v β 3 , the somatostatin receptor, the gastrin-releasing peptide receptor, melanoma and melanocortin-1 receptor, HER-2/neu receptor, VEGF receptor, and EGF receptor.…”
Section: Applications Of Zr Y Ga In and Cu Radiopharmaceuticalsmentioning
confidence: 99%
“…While several of the radiometals such as 67 Cu and 90 Y are used in oncology as radiotherapeutics, the remainder of this discussion will focus on the incorporation of In, Cu, Ga, Y, and Zr radiometals into radiopharmaceuticals for the diagnostic imaging of cancer. Moreover, while numerous radiopharmaceuticals have been prepared to detect biomarkers such as the folate receptor, ,, the neurotensin receptor, , oxytocin receptor expressing tumors, apoptosis using annexin-5, urokinase-type plasminogen activator receptor (uPAR), matrix metalloproteinases (MMPs), , Met-expression, antigens in head-and-neck cancer, , lymphoma, non-Hodgkin’s lymphoma, and esophageal and pancreatic cancer, , the remainder of this discussion will be further confined to several biomarkers that have received the most attention and include the integrin α v β 3 , the somatostatin receptor, the gastrin-releasing peptide receptor, melanoma and melanocortin-1 receptor, HER-2/neu receptor, VEGF receptor, and EGF receptor.…”
Section: Applications Of Zr Y Ga In and Cu Radiopharmaceuticalsmentioning
confidence: 99%
“…Single photon emission computed tomography (SPECT) and positron-emission tomography (PET) are imaging techniques that supply functional information, but they involve radiation exposure and are expensive with low availability and are hampered by relatively low spatial resolution [10–13]. …”
Section: Introductionmentioning
confidence: 99%
“…It was found that cancer cells uptake several times more iron-loaded transferrin than normal cells and that transferrin may be used as effective tumor targeting for nanosized delivery devices [68,[83][84][85]. In fact, the use of transferrin in nuclear medicine dates back many years ago because the use of 67 Ga and 68 Ga citrate complexes for the imaging of tumor and inflammation lesions [86][87][88] is based on the fact that Ga 3+ forms stronger complex with transferrin than Fe 3+ and is transported into tumor tissue by the transferrin-mediated way. The main drawback of transferin as a targeting moiety is its relatively high normal concentration in blood plasma (for a healthy adult human 2-4 g/L from which 30% is iron-loaded) which competes with the transferrin-targeted delivery device and necessity to isolate this protein from blood plasma (however, since the transferrin receptor binding peptide sequence has been elucidated, transferrin may be substituted by the oligopeptide sequence HAIYPRH [84]).…”
Section: Nanoparticles For Cancermentioning
confidence: 99%